‘I will re-create Finnegans Wake anyway’: Joseph Beuys reads James Joyce - Lerm Hayes, Christa-Maria (Nordic Journal of English Studies, 2018)
How did Joseph Beuys read James Joyce’s work? Beuys’ annotated copy of Finnegans Wake, as well as ‘Ulysses Extension’ drawings provide close insight into the artist’s thinking. Beuys’ work expands or ‘furthers’ Joyce in sculptural substances, language and by social means. Beuys used Joyce, especially Finnegans Wake, as a reference point of extraordinary suggestive power for the duration of his artistic career. Beuys’ current reappraisal lets us better understand his importance in pioneering ecological practices, in conceiving of art as an eco-system that sustains discursive and societal ‘force fields’— and, through this, glimpse possibilities for grasping Joyce’s ideal, indirect efficacy today.